Advanced cardiac life support : a guide for nurses - Jevon, Philip; Pooni, J. S. [ (Jagtar Singh)] (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2010)
* An evidence-based approach to emergency care based on the latest Resuscitation guidelines * A succinct yet comprehensive guide to the management of cardiac arrest * Written by an experienced resuscitation training offer who is also a qualified nurse and former CCU Charge Nurse.
1. Resuscitation service : an overview -- 2. Resuscitation equipment -- 3. Recognition and treatment of the critically ill patient -- 4. Principles of cardiac monitoring and ECG recognition -- 5. Bystander basic life support -- 6. Airway management and ventilation -- 7. Defibrillation and electrical cardioversion -- 8. Advanced life support -- 9. Resuscitation in special situations -- 10. Anaphylaxis -- 11. Acute coronary syndromes -- 12. Management of peri-arrest arrhythmias -- 13. Post-resuscitation care -- 14. Bereavement -- 15. Ethical issues in resuscitation -- 16. Resuscitation records -- 17. Resuscitation training
Includes bibliographical references and index
Keywords: Cardiac intensive care; Cardiovascular system -- Diseases -- Nursing; Advanced Cardiac Life Support -- methods; Advanced Cardiac Life Support -- nursing; Nursing Care -- methods